Export Composition and Economic Growth in Sub-Saharan Africa: A Panel Analysis - Bbaale, Edward; Mutenyo, John (Consilience, 2011)
This paper was guided by the hypothesis that it is not exports per se that matter, but different export components influence growth differently. We considered a sample of 35 sub-Sahara African countries based on availability of data on the key variables. Aggregate data were obtained from the most recent World Bank‟s World Development Indicators and International Monetary Fund‟s International Finance Statistics online facilities. Disaggregated data on exports and imports were obtained from the United Nation‟s Statistical Database under Standard International Trade Classification (SITC) Revision 4. The Generalized Methods of Moments estimator was employed during the analysis. We find that it is the growth in agricultural exports, and not manufactured exports, that is significantly associated with per capita income growth in our sample. These countries should adopt policies that increase agricultural exports in the medium term as they design strategies for increasing manufactured exports in the long term. Other factors significantly influencing growth are gross capital formation, capital goods imports, infrastructure, government consumption, and inflation rate, political systems and governance, and education.